Structural analysis of stone masonry columns of the Basilica S. Maria di Collemaggio. (15th December 2016) - Crespi, Pietro; Franchi, Alberto; Giordano, Nicola; Scamardo, Manuela; Ronca, Paola
Highlights: The architectonical and structural evolution of the church are described. The effects of past earthquakes are discussed. Response spectrum and eigenvalue analyses result is presented. Two different non-linear analyses are carried out on one representative nave column. Comparison between analytical and finite element approaches are discussed. Abstract: The Basilica of Collemaggio in L'Aquila is one of the outstanding architectural heritage in Abruzzo Region. The church, built in the late XIII century, has experienced many earthquakes during its life, some of which caused damages to the masonry structures, requiring continuous interventions and renovations. The last strong earthquake (April 6th, 2009) caused the collapse of the transept structures and significant damages in the apses area. Since 2009, several research groups have focused their attention on the Basilica, both from architectural and structural point of view. Particularly, recent studies have pointed out the historical value of nave columns, which seem to be XIII century authentic elements. Despite the magnitude of the last earthquake, the columns have proved limited resistance against seismic loads, resulting in a widespread damage, but without reaching the collapse. The aim of the present paper is to understand their structural behavior under horizontal actions. An overall finite element model of the church has been developed to perform eigenvalue and response spectrum analyses of the Basilica. Afterwards, a representative nave column has been studied considering both geometrical and mechanical non-linearity. In order to obtain a reliable evaluation of its structural behavior, two different models have been developed: an analytical model and a solid-brick finite element one. The performed analyses have allowed the evaluation of the stresses redistribution inside the columns after cracking. The results, provided in terms of force–displacement curve and stress contours, have permitted to identify some possible explanations about the columns seismic response.